Analysis of Potential Influence of Design, Procurement and Implementation Management Models on Cost Ineeficiency due to Building Construction Waste Materials Based on SEM Analysist - James Thoengsal (Budapest International Research and Critics University, 2022)
The emergence of residual materials during the building construction process cannot be avoided by the construction operator, especially the impact that directly or indirectly results in wasting construction material costs. However, this can be minimized by applying an ideal waste material management concept from the planning, procurement to implementation stages. The purpose of this study is to analyze the level of potential impact of the application of the concept of waste management of building construction materials in an effort to reduce the impact of inefficiency in project material costs, where in this study is viewed from the point of view of the parties involved in the project carried out by the State Owned Contractor (SOE). The method used in this research is done by distributing questionnaires to the building construction organizers which are being handled by the SOE contractors, where the respondents consist of experienced and responsible parties in project activities. So the conclusion from the results of this study shows that the concept of the model provides an impact test value that is quite ideal and has the potential to be applied by construction operators, both contractors, planning consultants and material suppliers in an effort to reduce the impact of cost inefficiency due to the emergence of residual building construction materials in Indonesia in the future.